Elucidating the toll-like receptor 4 involvement in striatum and cerebellum of swiss albino adult mice on motor and sickness behaviours - Wahab, Dayang Yasmin Abang Abdul (2018)
Alcohol addiction is one of the possible factors in stimulating brain microglia activation and leading to neuroinflammation through toll-like receptors (TLR) which are present in microglia. In fact, alcohol addiction ultimately causes motor deficits through neuroinflammation. However, the underlying mechanisms of neuroinflammation inducing motor behaviour through activation of TLR4 receptors have not yet been elucidated. TLR are always found to be associated or involved in the induction of neuroinflammation in neurodegenerative diseases. TLR4 is stimulated by TLR4 Agonist, Lipopolysaccharide (LPS), and the TLR4-LPS interaction has been found to result in physiological and behavioural changes including retardation of motor activity in the mouse model. Therefore, the present study aimed to investigate the locomotor behaviour, gene expression of serotonin receptors (HTR1A and HTR2A), dopamine receptors (Dopamine D1 receptor and Dopamine D2 receptor) and glutamate transporters (EAAT1 and EAAT4) in the striatum and cerebellum following treatment with TLR4 agonist. The animals were divided into three groups; (1) Control (n=12), (2) LPS treatment (0.83mg/kg) (n=12) 6 h and (3) LPS treatment (0.83mg/kg) (n=12) 24 h. After treatment, locomotor behaviour was analysed in open field test, wooden beam test and hanging test at 6 and 24 h post-LPS administration. Following behaviour test, animal’s brains were harvested and striatum and cerebellum isolated for gene expression studies. Results showed that there were locomotor deficits at 6 h but not in 24 h. The gene expression studies suggested that there were significant changes in serotonin receptors (HTR1A and HTR2A), dopamine receptors (Dopamine D1 receptor and Dopamine D2 receptor) and glutamate (EAAT1 and EAAT4) transporters in the striatum and cerebellum along with motor deficits. In conclusion,TLR4 possibly causes motor deficits through regulation of glutamate transporter EAAT1 in striatum and cerebellum.